Transglobal Leadership as a Framework for Environmental Policy Diplomacy in Addressing Transboundary Forest Fire Impacts: Evidence from Malaysia and Indonesia - Jaes, Lutfan; Rahman, Riki; Syamsuadi, Amir; Safitri, Kinanti Indah (Journal of Social Transformation and Regional Development, 2026)
Transboundary forest fires remain one of Southeast Asia’s most persistent ecological and diplomatic challenges. Despite existing mechanisms under the ASEAN Agreement on Transboundary Haze Pollution (AATHP), regional responses remain largely voluntary and norm-driven with limited enforcement capacity. This study proposes transglobal leadership as a strategic framework to strengthen environmental policy diplomacy across borders. Using a qualitative descriptive approach complemented by bibliometric mapping (2015–2025), the research identifies the evolving intellectual landscape of transglobal leadership and its applicability to environmental governance. The findings reveal that effective transboundary haze management requires five core leadership values such as: strategic global vision, adaptive resilience, ethical responsibility, collaborative diplomacy, and knowledge-based innovation operationalized through adaptive, integrative, and collaborative mechanisms. Empirical evidence from Malaysia and Indonesia cooperation demonstrates partial progress in institutionalized coordination and shared environmental norms but highlights the need for binding accountability and deeper polycentric governance. The study concludes that embedding transglobal leadership values into ASEAN’s environmental diplomacy could transform the region’s haze management from reactive coordination into proactive and knowledge-driven ecological governance.